2017
DOI: 10.1186/s13048-017-0307-6
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 expression, proliferative and apoptotic activities in ovarian epithelial inclusions

Abstract: BackgroundThe purpose of this study was to examine proliferative and apoptotic activity in relation with BRCA1 expression in ovarian epithelial inclusions (OEIs), the putative precursor lesions of ovarian epithelial cancer (OEC).MethodsBenign ovaries from 95 patients were examined. Dual immunohistochemical staining for both BRCA1 and MIB-1 were performed to examine the relationship between BRCA1 and MIB-1 in OEI cells. Apoptotic activity was assessed on the parallel tissue sections by using TUNEL assay. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…These findings provide evidence to support the conclusion that PRRX1 is a target gene of miR-1307. Up to now, several important genes involved in tumorigenesis had been identified as the target genes of miR-1307, such as BCL2 20 , TYMS 21 , MDM4 32 , SMYD4 23 , DAB2IP 24 , FOXO3A 25 , ING5 26 , and ISM1 33 , indicating critical roles of miR-1307 in cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings provide evidence to support the conclusion that PRRX1 is a target gene of miR-1307. Up to now, several important genes involved in tumorigenesis had been identified as the target genes of miR-1307, such as BCL2 20 , TYMS 21 , MDM4 32 , SMYD4 23 , DAB2IP 24 , FOXO3A 25 , ING5 26 , and ISM1 33 , indicating critical roles of miR-1307 in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al provided evidence to support that miR-1307 played a very important role in the progression of liver cancer by targeting DAB2IP 24 . Moreover, studies demonstrated that miR-1307 boosted the progression of prostate cancer by targeting FOXO3A 25 and induced chemoresistance of ovarian cancer cells by inhibiting ING5 26 .…”
Section: Introductionmentioning
confidence: 99%